Hot flushes - Jacky van Schoor (South African Family Practice)
Vasomotor symptoms, such as hot flushes and night sweats, are considered to be the cardinal symptoms of menopause, and are experienced by most women. The physiology of hot flushes is not fully understood, and is likely to reflect the interplay between multiple central and peripheral physiological systems. Reproductive hormones play an integral role, as evidenced by the onset of vasomotor symptoms during the dramatic reproductive hormone changes of the menopausal transition, and by the efficacy of exogenous oestrogen in the treatment of hot flushes. Menopausal hormone therapy with oestrogen, and with or without a progestogen, is the most widely studied and most effective treatment option for the relief of menopause-related vasomotor symptoms. It is also considered to be the standard of care for women with moderate to severe vasomotor symptoms.